Utilização de aplicativos móveis para o sintoma zumbido - Barboza, Hionara Nascimento (2022)
Introduction: Tinnitus is a perception of sound in the absence of an external stimulus. It can be perceived in one ear, in both ears or in the head. Much has been discussed about new tools to help in the evaluation and treatment of tinnitus, such as innovation of therapeutic techniques and evaluation methods, being the technological innovation a great ally for the development of these tools. Thus, applications (apps) are tools that have expanded in the health area. In what concerns the tinnitus area, it is no different, apps are being developed to help in the treatment and evaluation of the symptom. Thus, it becomes necessary to carry out usability tests to verify the effectiveness, efficiency and user satisfaction, with the purpose of providing a scientifically proven application. Objective: To carry out a survey about the existing tinnitus applications, as well as to carry out usability tests of the tinnitus assessment application Avazum. Methodology: This dissertation is structured in two scientific articles. Article 1 is entitled "Tinnitus mobile applications: an integrative review". It is an integrative review study that had as its main objective to carry out a survey about the existing applications for tinnitus, from the search in the application stores, as well as, to analyze the studies about the theme from the literature search. Article 2 is entitled "Usability test of the tinnitus evaluation application (Avazum). It is a usability study, in which it aimed to perform the testing of the tinnitus assessment app (Avazum). Results: Regarding the search in the two app stores, it was possible to select 43 apps in total on the two main systems surveyed, android and iOS. The apps offer three main functions, sound therapy, mindfulness, and tinnitus assessment. No assessment apps with a multi-professional interface were found, and few performed usability testing. Regarding the avazum usability test, it was carried out with the participation of 48 tinnitus users. Thus, the average score in the System Usability Questionnaire (SUS) was 78.28 being consistent with a satisfactory average score, which implies that the application does not present serious usability problems, as well as 58% in the Net Promoter Score (NPS), which indicates a very good satisfaction of users, as well as 66% of promoter users, those who liked the application and help in dissemination. With respect to effectiveness, it was possible to observe that Avazum reaches the proposed objectives, besides being efficient, because it presents a clear language and comfortability during use. Final Considerations: Thus, it is possible to notice that there are no assessment apps with a multi-professional interface, with a referral function for users and tips and guidance such as Avazum, available in app stores, besides few apps tested for tinnitus. And the usability test of Avazum obtained satisfactory results, showing good usability and effectiveness, with clear language and ease of use.